2022
DOI: 10.1111/ijpo.12883
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity associated with weight status in 9 to 10 year old children

Abstract: Summary Background Paediatric overweight and obesity (OW/OB) constitute a serious public health concern. Given that psychological problems may be key contributors to the onset and maintenance of paediatric obesity, the present study examined past and current psychiatric comorbidities across the weight spectrum during middle childhood among a nationally representative sample. Methods Participants were 11 708 9‐ to 10‐year‐old children (31.6% with OW/OB) and their caregivers who participated in the first wave of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…Pese a la indicación de la necesidad de determinar mediciones de fácil detección y bajo costo, se han usado instrumentos como K-SAD (Kiddie Schedule for Affective Disorders and Schizophrenia). Estas mediciones han sido efectuadas por profesionales especializados de América Latina, donde se encuentra la asociación más significativa entre exceso de peso y trastornos depresivos, atracones, ansiedad por separación y trastorno por estrés postraumático, sin determinar causalidad (31). Dicho instrumento es una herramienta de diagnóstico, más que de tamización.…”
Section: Discussionunclassified
“…Pese a la indicación de la necesidad de determinar mediciones de fácil detección y bajo costo, se han usado instrumentos como K-SAD (Kiddie Schedule for Affective Disorders and Schizophrenia). Estas mediciones han sido efectuadas por profesionales especializados de América Latina, donde se encuentra la asociación más significativa entre exceso de peso y trastornos depresivos, atracones, ansiedad por separación y trastorno por estrés postraumático, sin determinar causalidad (31). Dicho instrumento es una herramienta de diagnóstico, más que de tamización.…”
Section: Discussionunclassified
“…For instance, one recent study reported that not overweight/obesity per se exerted negative impact on EF performance [ 14 ]. Importantly, few research has investigated EF impairments across weight spectrum (e.g., underweight, normal, overweight/obesity) [ 15 ] in adolescents, especially those with underweight condition. In the meantime, most studies had a limited sample size (often by case–control study design), only used the BMI indicator (less sensitive to body fat [ 16 ]) to assess overweight/obesity condition, and often neglected the group with underweight state that likely present with a lower EF score [ 17 ].…”
Section: Introductionmentioning
confidence: 99%